The social work and the pandemic: prospective reflections: https://doi.org/10.53809/2021-01-TS-n.1-7-30 ("Temas Sociais" Journal, 2021)
The aim of this text is to initiate an exploratory reflection on the lessons learnt from the pandemic, possibly useful in the qualification of social work practices.We will begin by describing in general terms the impact of the pandemic on contemporary society, on three scales of complexity: micro, meso and macro. Next, some exploratory reflections will be made on the role of social work in the pandemic, based on a brief analysis of available documents and indirect observation. In a third moment, we will try to draw some lessons that allow us to collectively face a future full of uncertainties and threats, but also opportunities to overcome them.
Keywords: pandemic Covid 19; black swan; informational fog; social responsibility; foresight